Desinformação nas eleições de 2022: uma abordagem biopolítica sobre a ofensiva contra as urnas eletrônicas - Barreto, Alana Maria Passos (2025)
How did the disinformative discourse of “fraud in electronic voting machines” infect the 2022 elections? To answer this question, the hypothesis is adopted that there was a disinformation attack by presidential candidate Jair Bolsonaro (at the time of the Liberal Party), based on systematically spread lies attributed to an alleged “fraud” in the 2022 elections. In this sense, investigating the expressiveness and narrative configuration of disinformation about the Brazilian electoral process, which spreads as a social contagion, will allow us to understand the discourse of digital populism, represented in this study by Jair Bolsonaro, triggered by false stories that essentially focused on the symbolic representation of Brazilian democracy, which is, therefore, the electronic voting machines. This contagion is characterized by imitation and the mobilization of opinions and feelings, whether they are supporters or opponents. Due to the problem demonstrated, an essentially qualitative approach will be used to achieve the proposed objective combined with bibliographic and documentary procedures, which will accompany all stages of research development. However, within the scope of empirical research, this work did not suffice, this work used virtual ethnography together with qualitative content analysis and the three-dimensional model of critical discourse analysis by Norman Fairclough (2001). This dissertation adheres to the large area of concentration on the Constitutionalization of Law. It is inserted in the line of research into the effectiveness of fundamental rights and their impact on social and business relations.